Hierarchical self-assembly of nematic colloidal superstructures. - Skarabot, M; Ravnik, M; Zumer, S; Tkalec, U; Poberaj, I; Babic, D; Musevic, I (2008)
We show that colloidal superstructures could be assembled in mixtures of large and small colloidal particles dispersed in a nematic liquid crystal. Using elastic interaction of small colloidal particles with the disclination lines we succeed to demonstrate how one can decorate with small particles a topological matrix of defect rings and loops formed by an array of large colloidal particles. Our simulations show that this concept of colloidal self-assembly in nematics could be extended down to the nanoscale particles.